The Effect of Carbon Organic Total and Salinity on The Discharge of Heavy Metals Pb and Cu in Lapindo Mud into The Aloo River - Alvin Juniawan; Barlah Rumhayati; Bambang Ismuyanto (The Journal of Pure and Applied Chemistry Research, 2012)
The research attempts to examine the effect of waters salinity and carbon organic total in the Lapindo Mud on the fluctuation of heavy metals Cu and Pb in the waters of Aloo Rivers. Sample is taken from Lapindo Mud from four different locations. Result of the characterization of Lapindo Mud shows that the clay and dust contents are 34-35 % and 39-46 %. Lapindo Mud texture is clay loam. The organic matter in Lapindo Mud is not surely increasing the concentration of heavy metal because there is oxide compound with great contribution to the increase of heavy metal concentration in Lapindo Mud. Result of TOC analysis indicates that the organic carbon ranges from 54.7 % to 55.47 %, Pb rate ranges from 0.27-0.34 mg/L, and Cu rate ranges from 0.83-1.31 mg/L. Indeed, Pb has higher metal flux in salt water at AL from 5x10-5 mg/cm2.hour to 9x10-5 mg/cm2.hour. Cu has higher metal flux in freshwater at SA1 2.3x10-6mg/cm2.hour to 8.71x10-5mg/cm2.hour